Caracterização de leguminosas arbustivo-arbóreas em Pernambuco - SILVA, Mônica Alixandrina da (2011)
Experiments investigating the characteristics of forage legume were carried out in 2007 and 2008 at the Experimental Station in Itambe and São Bento do Una, both belonging to the State of Pernambuco Institute Agricultural Research Corporation, Brazil (IPA). The first experiment set out to characterize the morphology and quality of three plantations, each containing legumes comprising Mimosa caesalpinifolia Benth. (Sabiá) and Machaerium aculeatum Raddi (Espinheiro) in Itambe, and Bauhinia cheilantha (Bong.) Steud. (Mororó) in São Bento do Una. Simple description techniques were used, as well as more complex ones, such as path correlation and analysis. At the end of the morphological evaluation, specimens of leaves and stalks were collected (< 4mm) to determine the chemical composition and digestibility in vitro of the dry matter. The second experiment took place in 2008 in the town of Itambé-PE, with the intention of characterizing the Sabiá, Mororó e leucena legumes which were two years old at the start of the experiment. Uniform cutting was carried out, and every seventy days the production of dry matter, morphology and chemical composition were determined. At the end of the evaluations, leaves were collected to determine the degradability in situ and the folic anatomy. The majority of variables correlated positively with the in vitro digestibility of the dry matter of the three species evaluated. Sabiá, Mororó and Espinheiro proved to be very heterogeneous in relation to their morphological variables. The legumes presented high levels of dry material, crude protein, and fibre in neutral detergent, fibre in acidic detergent and digestibility of dry matter in vitro. With path analysis it was observed that the crude protein variable was responsible for the in vitro increase in digestibility of the dry matter. It was observed that, for morphological and productive characteristics, the species differed among each other and among evaluation periods, resulting in values between 1.4 and 4.4 t of MS/ha/cutting: 1.44 to 2.76m in height; 6.6 to 25.2 leaves/branch; 0.95 to 1.51m in the diameter of the crown and 24.9 to 43.3cms in diameter at the base of the trunk. Leaf cross sections of Sabiá revealed highly lignificated materials which differed from those of the Leucena and Mororó. There was a greater degradation in the leaves of Leucena, Sabiá and Mororó respectively. The legumes presented high levels of crude protein and low levels of digestibility in vitro of dry matter. In relation to the production of dry matter, there was a low correlation between almost all the explicative variables and the principal variable in the legumes studied. However, the height and crown diameter (Leucena), number of leaves and crown diameter (Mororó) and height and crown diameter (Sabiá) better explain the production potential of dry matter which interferes directly or indirectly with the dependent variable. This indicates that those who wish to select plants with high production of dry matter should select characteristics such as height, crown diameter and number of leaves.